Pengaruh Kompetensi dan Kualtas Kerja Terhadap Prestasi Kerja Pegawai di Kantor Camat Soromandi Kabupaten Bima - Bagus Shaburu; Kartin Aprianti; Khairul Amar (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: This study aims to determine the effect of competence and work quality on employee work performance at the Soromandi Sub-district Office, Bima Regency. Background of the Problem: The Soromandi Sub-district Office as one of the government units in Bima Regency has a strategic role in providing administrative services and government management so that it requires good competence and work quality. Novelty: Different from previous studies, examining the same variables but focusing on employee work performance in the agency. Research Method: This study uses a Likert scale questionnaire with a sample of 32 respondents. Findings/Results: Partially, only work quality has a significant effect on work performance, but simultaneously, competence and work quality have a significant effect on employee work performance at the Soromandi Sub-district Office, Bima Regency. Conclusion: High employee competence and good work quality reflect professionalism, responsibility, and commitment to work so that it can improve employee work performance.